Design and fabrication of electronic housing for water filter membrane module via 3D printing - Jaw, Wei Qi (Nanyang Technological University, 2022)
As a small nation with limited natural resources, water is a precious and scarce resource. The quest for Singapore’s water sustainability has been one of the country’s main priorities, and this led to the development of NEWater. NEWater recycles used water into high grade reclaimed water through advanced membrane filtration technologies like Reverse Osmosis. Despite the benefits of membrane technologies, micro-organisms present in wastewater results in a major challenge to the use of membrane technologies due to membrane fouling. Non-invasive detection methods like Electrical Impedance Spectroscopy are used for real time detection of membrane fouling. However, a successful operation is hampered by water hammering. Water hammering results in violent vibrations that dislodge and damage the electronic components. The project aims to improve the design of the Anti-Telescoping Device, which the electronic components are attached onto. For the project, different vibration damping materials and lattice structures will be explored to investigate the effectiveness of different combinations of lattices and material in absorbing vibration. Computer Aided Design software was used to generate the new designs and for analysis, the Finite Element Analysis software, ANSYS will be for numerical simulation. From the results obtained from Harmonic Response Analysis and Transient Structural Analysis, it showed that lattice structures were able to provide vibration absorbing capabilities. Comparing between original and modified designs, the modified designs were able to reduce the stress and deformation experienced by at least 50% and 20% respectively. Among all the designs tested, the combination with larger lattice structures, together with a more flexible material, TPU, offered the best vibration absorbing capability. To realise the conceptualisation of the designs, 3D Printing technologies like Fused Deposition Modelling (FDM) and Digital Light Processing (DLP) were selected as the fabrication method. Both FDM and DLP proved to be capable in printing the lattice structures. However, there were defects like warping and delamination for the FDM and difficulties post curing for the DLP. Future work will include optimising the printing parameters to obtain a nicely printed lattice structures for both the rigid and flexible material. With the 3D printed model, physical testing can be done with a Vibration Exciter Machine to validate the simulated results.